Spontaneous coronary artery dissection: an unpredictable event. (21st April 2023) - Smirnova, Alexandra; Aliberti, Flaminia; Cavaliere, Claudia; Gatti, Ilaria; Vilardo, Viviana; Giorgianni, Carmelina; Cassani, Chiara; Repetto, Alessandra; Narula, Nupoor; Giuliani, Lorenzo; Urtis, Mario; Ozaki, Yukio; et al.
Abstract: Spontaneous coronary artery dissection (SCAD) is an under-recognized cause of acute coronary syndrome that predominantly affects women in adulthood and is the leading cause of acute myocardial infarction in pregnancy. The most common clinical presentation is ST-segment elevation myocardial infarction (STEMI) or non-STEMI, followed by cardiogenic shock (∼2%), sudden cardiac death (0.8% in autopsy series), cardiac arrest, ventricular arrhythmias (∼5%), and Takotsubo syndrome. The prevalence of SCAD in the general population is largely uncertain due to underdiagnosis. Oral contraceptives, post-menopausal therapy, and infertility treatments are recognized associated factors. The pathological substrates (fibromuscular dysplasia) and triggers (especially emotional stress) are commonly present in affected women. The few cases with a precise genetic aetiology occur in the context of syndromic and non-syndromic connective tissue diseases. The only true certainty in SCAD is the overwhelming prevalence in women. The first event as well as the recurrence (up to 30%, which varies depending on the definition) is largely unpredictable. The treatment strategy is highly individualized and requires extensive additional study in order to optimize outcomes and prevent major adverse cardiovascular events in affected individuals. We have known about SCAD for nearly a century, but we still do not know how best to prevent, diagnose, and treat it, making SCAD a highly important and unmet clinical need.